Proatherogenic Flow Increases Endothelial Stiffness via Enhanced CD36-Mediated Uptake of Oxidized Low-Density Lipoproteins. Issue 1 (January 2018) - Le Master, Elizabeth; Huang, Ru-Ting; Zhang, Chongxu; Bogachkov, Yedida; Coles, Cassandre; Shentu, Tzu-Pin; Sheng, Yue; Fancher, Ibra S.; Ng, Carlos; Christoforidis, Theodore; Subbaiah, Pappasani V.; Berdyshev, Evgeny; et al.
Abstract : Objective—: Disturbed flow (DF) is well-known to induce endothelial dysfunction and synergistically with plasma dyslipidemia facilitate plaque formation. Little is known, however, about the synergistic impact of DF and dyslipidemia on endothelial biomechanics. Our goal was to determine the impact of DF on endothelial stiffness and evaluate the role of dyslipidemia/oxLDL (oxidized low-density lipoprotein) in this process. Approach and Results—: Endothelial elastic modulus of intact mouse aortas ex vivo and of human aortic endothelial cells exposed to laminar flow or DF was measured using atomic force microscopy. Endothelial monolayer of the aortic arch is found to be significantly stiffer than the descending aorta (4.2+1.1 versus 2.5+0.2 kPa for aortic arch versus descending aorta) in mice maintained on low-fat diet. This effect is significantly exacerbated by short-term high-fat diet (8.7+2.5 versus 4.5+1.2 kPa for aortic arch versus descending aorta). Exposure of human aortic endothelial cells to DF in vitro resulted in 50% increase in oxLDL uptake and significant endothelial stiffening in the presence but not in the absence of oxLDL. DF also increased the expression of oxLDL receptor CD36 (cluster of differentiation 36), whereas downregulation of CD36 abrogated DF-induced endothelial oxLDL uptake and stiffening. Furthermore, genetic deficiency of CD36 abrogated endothelial stiffening in the aortic arch in vivo in mice fed either low-fat diet or high-fat diet. We also show that the loss of endothelial stiffening in CD36 knockout aortas is not mediated by the loss of CD36 in circulating cells. Conclusions—: DF facilitates endothelial CD36-dependent uptake of oxidized lipids resulting in local increase of endothelial stiffness in proatherogenic areas of the aorta. Abstract : Supplemental Digital Content is available in the text.